Effects of Red Coconut Tembuluk (Cocos nucifera var. rubescens) Extract on Creatinine Level Reduction in Mice (Mus musculus) - Amelia A Riuh; Sutrisnawati Sutrisnawati; Manap Trianto; Masrianih Masrianih; Fatmah Dhafir; I Nengah Kundera (Biology, Medicine, & Natural Product Chemistry, 2026)
Creatinine is a key biochemical indicator of renal function, and elevated creatinine levels reflect impaired kidney performance. Carbon tetrachloride (CCl4) is a known nephrotoxic agent that induces oxidative stress and renal damage. This study evaluate the effect of red coconut tembuluk (Cocos nucifera var. rubescens) extract on creatinine in CCl4-induced mice (Mus musculus). The study employed an experimental laboratory design using 24 male mice, which were divided into six groups: normal control, negative control (CCl4-induced), and four treatment groups administered red coconut tembuluk extract at concentrations of 10%, 20%, 40%, and 80%. Renal damage was induced by intraperitoneal injection of CCl4 at a dose of 1 mL/kg body weight. The extract was administered orally for eight consecutive days following induction. Serum creatinine levels were measured before and after treatment. The results showed that CCl4 induction significantly increased creatinine levels in the negative control group compared to the normal control, indicating impaired renal function. Administration of red coconut tembuluk extract resulted in a significant reduction in creatinine levels across all treatment groups, with the most pronounced effect observed at the 80% concentration. Statistical analysis using one-way ANOVA demonstrated a significant effect of the extract on creatinine reduction (p < 0.05), followed by a Least Significant Difference (LSD) test confirming differences among treatment groups. The nephroprotective effect of the extract is likely associated with its bioactive compounds, including flavonoids, antioxidants, and L-arginine, which contribute to the reduction of oxidative stress and support renal tissue recovery. In conclusion, red coconut tembuluk extract effectively reduces serum creatinine levels in CCl4-induced mice, with the 80% concentration showing the greatest protective effect. These findings suggest that red coconut tembuluk has potential as a natural nephroprotective agent.